Prospective Science Teachers’ Problem-solving Skills through Science-integrated Learning (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
Problem-solving skills require an integrated understanding of the data, facts, and scientific theories being studied. Prospective teachers need problem-solving skills so that their way of thinking becomes more critical and analytical. This study aims to measure prospective science teachers’ problem-solving skills after applying the science-integrated learning model. This study uses a mixed method. Quantitative data in this study were obtained from the test results measuring problem-solving skills. Qualitative data were obtained from exploring the test results through in-depth interviews with respondents. Prospective science teachers have excellent problem-solving skills. The average score is 86, the highest score is 92, and the lowest score is 80. Most students get a score >85, and there are no students who score below 80. This study concludes that problem-solving skills are measured from various prospective science teachers’ learning outcomes through practicum, discussion, and assignments.